Alteration in blood leukocyte profile due to exercise and its implication - Ryoichi Nagatomi (Japanese Society of Physical Fitness and Sports Medicine, 2013)
Evaluation of peripheral blood leukocytes has been considered a popular window to the immune system and its response. The numeration of leukocytes has long been a practical clinical marker of acute inflammation. Yet, the numbers and function of circulating leukocytes may also change during and after exercise to an extent comparable to inflammatory responses. A considerable amount of effort to elucidate the underlying mechanism of such changes in circulating leukocytes, however, has revealed quite a different picture showing a major contribution of the neuroendocrine system independent of inflammatory processes. Interestingly, a good correlation of the blood leukocyte profile with athletic performance in endurance runners was reported. It is therefore important to understand and interpret observed changes depending on the context to avoid misinterpretation, especially regarding potential immunological risks unlikely to happen from exercise. A review of the literature, therefore, suggests a minor or negligible immune perturbation of exercise.